Tinjauan Kaidah Fikih “Dar’ul Mafasid Muqaddamun ‘Ala Jalbil Masholih” terhadap Profesi Manusia Silver di Sekitar Jalan Pasteur Bandung - Nadhifa Ayusha Lesmana; Sandy Rizki Febriadi (UNISBA Press, 2022)
Abstract. Humans need to work. In Islam, jobs must be in accordance with the Shari'ah. Nowadays, many jobs have much risks. One of them is the silver man. In practice, the silver man covered his entire body with silver paint and speech to gain sympathy from local people. Meanwhile, the main ingredients of silver paint itself comes from screen printing paint mixed with supporting materials such as wheat flour and kerosene. If used continuously, the silver paint will cause diseases such as skin cancer, paralysis, and even death. This study aims to determine the review of fiqh rules